SOCIAL-EMOTIONAL EDUCATION AS AN INNOVATIVE PEDAGOGICAL PHENOMENON - Safarova, R.G (Journal of Learning on History and Social Sciences, 2025)
Objective: To analyze the distinctive characteristics, pedagogical significance, and implementation conditions of social-emotional education, as well as to identify the essential knowledge, skills, and competencies it cultivates in students. Method: A comprehensive literature review and analysis of empirical studies were conducted to synthesize current theoretical frameworks and practical approaches in the field. Results: The findings indicate that social-emotional education enhances individual well-being and fosters societal cohesion by promoting interpersonal competencies and academic success, thereby affirming its critical role in modern education. Novelty: This work provides a novel integration of theoretical insights and empirical evidence, offering a robust framework that informs educators, policymakers, and researchers on effectively incorporating social-emotional learning into diverse educational contexts.